Integrity and the virtues of reason leading a convincing life - Scherkoske, Greg 1969- (Cambridge University Press, 2013)
"Many people have claimed that integrity requires sticking to one's convictions, come what may. Greg Scherkoske challenges this claim, arguing that it creates problems in distinguishing integrity from fanaticism, close-mindedness, or mere inertia." -- Back cover